Application of crosslinked polybenzimidazole-poly(Vinyl benzyl chloride) anion exchange membranes in direct ethanol fuel cells - Herranz, Daniel (2020)
Crosslinked membranes have been synthesized by a casting process using polybenzimidazole (PBI) and poly(vinyl benzyl chloride) (PVBC). The membranes were quaternized with 1,4-diazabicyclo[2.2.2]octane (DABCO) to obtain fixed positive quaternary ammonium groups. XPS analysis has showed insights into the changes from crosslinked to quaternized membranes, demonstrating that the crosslinking reaction and the incorporation of DABCO have occurred, while the13C-NMR corroborates the reaction of DABCO with PVBC only by one nitrogen atom. Mechanical properties were evaluated, obtaining maximum stress values around 72 MPa and 40 MPa for crosslinked and quaternized membranes, respectively. Resistance to oxidative media was also satisfactory and the membranes were evaluated in single direct ethanol fuel cell. PBI-c-PVBC/OH 1:2 membrane obtained 66 mW cm−2 peak power density, 25% higher than commercial PBI membranes, using 0.5 bar backpressure of pure O2 in the cathode and 1 mL min−1 KOH 2M EtOH 2 M aqueous solution in the anode. When the pressure was increased, the best performance was obtained by the same membrane, reaching 70 mW cm−2 peak power density at 2 bar O2 backpressure. Based on the characterization and single cell performance, PBI-c-PVBC/OH membranes are considered promising candidates as anion exchange electrolytes for direct ethanol fuel cells.